The Effect of WhatsApp-Integrated Meta AI Chatbot on Vocational Students' Critical Thinking Skills in the Automotive Engineering Basic Subjects - Sumardi Sumardi; Yogi Yunefri; Zamzami Zamzami; Rizki Novendra; Yogo Turnandes; Safrianto Safrianto (AL-ISHLAH: Jurnal Pendidikan, 2026)
The integration of artificial intelligence (AI) into vocational education offers new opportunities to enhance students’ higher-order thinking skills, particularly critical thinking. However, empirical evidence on the effectiveness of AI chatbots in supporting critical thinking within vocational automotive learning remains limited. This study investigates the effect of a WhatsApp-integrated Meta AI chatbot on vocational students’ critical thinking skills in the Automotive Engineering Basic Subjects. This research employed a quantitative quasi-experimental design with a non-equivalent control group. The participants were 40 tenth-grade vocational high school students divided into an experimental group (n = 20) and a control group (n = 20). The experimental group used a Meta AI chatbot integrated with WhatsApp as a learning companion during four instructional sessions, while the control group received conventional instruction. Data were collected using a validated critical thinking test measuring analysis, evaluation, and inference skills. Statistical analysis included descriptive statistics, assumption tests, independent samples t-tests, N-gain analysis, and simple linear regression. The results indicate a significant difference in critical thinking scores between the experimental and control groups (t(38) = 2.466, p = 0.018). The effect size was categorized as medium-to-large (Cohen’s d = 0.78). The experimental group also showed a moderate improvement (N-gain = 0.45). Regression analysis revealed that the use of the Meta AI chatbot explained 18% of the variance in students’ critical thinking performance (R² = 0.18, p = 0.029). These findings suggest that integrating AI chatbots through widely used communication platforms such as WhatsApp can support the development of critical thinking in vocational education, particularly in technical problem-solving contexts.